Mid-term effect of Roux-en-Y gastric bypass on type 2 diabetes mellitus: a retrospective single surgeon observational study with focus on anti-diabetic medication - Gys, Ben; Haenen, Filip; Gys, Tobie; Lafullarde, Thierry (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2017)
Background/purpose: Few studies evaluating the mid-term outcome of type 2 diabetes mellitus (t2DM) after Roux-en-Y Gastric Bypass (RYGB) are available at this time. The aim of this study is to assess mid-term impact of RYGB on t2DM regarding the need for anti-diabetic medication, biochemical response and associated weight loss. Methods: Retrospective analysis of prospectively collected data was performed for patients suffering from t2DM who underwent RYGB between 1/1/2000 and 1/1/2015. Patients were divided into 2 groups according to the preoperative need for insulin. Study parameters included Body Mass Index (BMI), %Excess Weight Loss (%EWL), Hemoglobin A1c (HbA1c) and fasting glucose at 1, 3, 6 and 10-year intervals after surgery. Results: 140 patients (97 women, 43 men) were included. Mean preoperative BMI was 42.8 kg/m² (range 35.0 - 75.0). Mean duration of t2DM before RYGB was 5,7 years (range 0,2 - 30,1). Preoperative need for anti-diabetic medication was seen in 102 patients (72,8%) of which 49 (48,0%) were insulin-dependent (ID-group). Mean postoperative follow-up was 5,9 years (range 0,1 – 14,5). Remission of t2DM (fasting glucose < 126mg/dl and a HbA1c < 6.5% without the need of anti-diabetic medication for at least 6 months) was present in both groups: 46,7%, 48,1%, 45,0%, 50,0% (ID-group) and 59,1%, 62,2%, 53,3%, 33,3% (insulin independent patients) at respectively 1, 3, 6 and 10-years follow up. No significant correlation was proven between remission and %EWL. Conclusions: Bariatric surgery is useful in the mid-term management of uncontrolled t2DM.